Thirteen new species and new distribution records of Helicopsyche (Feropsyche) Johanson from Venezuela (Trichoptera: Helicopsychidae) - Johanson, Kjell Arne; Holzenthal, Ralph W. (Zootaxa, 2004)
Thirteen new species of Helicopsyche subgenus Feropsyche are described and illustrated from Venezuela: H. auroa, new species, H. camuriensis, new species, H. circulata, new species, H. disjuncta, new species, H. laneblina, new species, H. lara, new species, H. linabena, new species, H. neblinensis, new species, H. perija, new species, H. succincta, new species, H. sucrensis, new species, H. tachira, new species, and H. venezuelensis, new species. In addition, new distribution records for Venezuela are reported for H. angulata Flint, H. breviterga Flint, H. extensa Ross, H. fistulata Flint, H. grenadensis Flint & Sykora, H. maculisternum Botosaneanu, H. merida Botosaneanu & Flint, H. monda Flint, H. selanderi Ross, H. vergelana Ross, and H. woytkowskii Ross. Finally, a key to males of the known species in the subgenus from Venezuela is included.